2016
DOI: 10.1152/jn.00876.2015
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric connectivity during bimanual isometric force generation

Abstract: Interhemispheric interactions through the corpus callosum play an important role in the control of bimanual forces. However, the extent to which physiological connections between primary motor cortices are modulated during increasing levels of bimanual force generation in intact humans remains poorly understood. Here we studied coherence between electroencephalographic (EEG) signals and the ipsilateral cortical silent period (iSP), two well-known measures of interhemispheric connectivity between motor cortices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 65 publications
2
24
0
2
Order By: Relevance
“…Finally, we calculated bipolar EEG montages based on the monopolar recordings to assess cortical activity from bilateral sensorimotor cortices: C3-F3 for the left sensorimotor cortex, and C4-F4 for the right sensorimotor cortex (cf. Long et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we calculated bipolar EEG montages based on the monopolar recordings to assess cortical activity from bilateral sensorimotor cortices: C3-F3 for the left sensorimotor cortex, and C4-F4 for the right sensorimotor cortex (cf. Long et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, EEG power in the beta frequency band as well as EEG sample entropy and fractal dimension of both left and right motor cortices shows a significant increase in postfatigue contraction than in prefatigue contraction. As movements of the right side of the body are mainly controlled by the left motor cortex of the brain and bilateral connection of upper limb movement [ 17 , 18 ], the increase of EEG power, sample entropy, and fractal dimension in both left and right motor cortices can be easily expected. However, significant phase synchronization index changes were only found between C3 and FC3, indicating that elbow flexion muscle fatigue may only have significant influences on the functional connectivity of the contralateral motor cortex during elbow extension contraction.…”
Section: Discussionmentioning
confidence: 99%
“…EEG oscillation activity in beta rhythm is associated with motor cortical function [ 17 , 19 , 20 ], and a significant increase of EEG-EMG and EMG-EMG coupling in the beta frequency band induced by muscle fatigue has been revealed in many studies [ 15 , 21 , 22 ]. In this study, a significant increase of the phase synchronization index was found in the beta frequency band between contralateral primary motor cortices, which suggested a significant role for synchronization in the organization and regulation of elbow extension movement within the contralateral primary motor cortex when the antagonist muscle prefatigued.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining components were retained and projected back onto the channels. Finally, we calculated bipolar EEG montages based on the monopolar recordings to assess cortical activity from bilateral sensorimotor cortices: C3-F3 for the left sensorimotor cortex, and C4-F4 for the right sensorimotor cortex 200 . A differential recording between electrode pairs suppresses far-field contamination and is hence most sensitive to local activity generated between the electrode pairs.…”
Section: Experimental Protocol Participants Performed Overground Walmentioning
confidence: 99%